WHEN IMPOSSIBLE HAPPENS - Suza, Jane De. (New York : G.P. Putnam's Sons, 2023)
When the pandemic hits and India goes lockdown, high-spirited almost-nine-year-old Swara keeps up her daily chats with her just-as-high-spirited grandmother, Pitter Paati, through video calls. But soon, Pitter Paati becomes to ill to even call, and then Swara's parents say her grandmother has died of the virus. Swara cannot believe it. It's impossible! Pitter Paati simply can't be gone for good. As Swara investigates her grandmother's disappearance, she stumbles upon a neighborhood history--right outside her window. And clues keep appearing that Swara is certain are coming from Pitter Paati. Is it possible that investigating one mystery might shed light on the other? Readers will fall in love with lively Swara in this poignant story that finds hope amid great loss and shows how even if someone important is gone, they can be with us forever.
Originally published by Penguin Random House India in 2021 under title: When the world went dark.
Keywords: Loss -- Fiction; Quarantine -- Fiction; Grandmothers -- Death -- Fiction; COVID-19 Pandemic, 2020 -- Fiction; Detective and mystery fiction